Self-perception in elite collegiate female gymnasts, cross-country runners, and track-and-field athletes - Saint-Phard, D.; Van Dorsten, B.; Marx, R. G.; York, K. A. (Mayo Clinic Proceedings, 1999)
To compare self-perception between a group of competitive, elite female collegiate athletes (participating in gymnastics, cross country, and track and field) and a group of female political science students (nonathletic control subjects). We hypothesized that the athletic group would rate athletics as more important than would the nonathletic group, that the perception of athletic competence would correlate positively with self-worth for athletes only, and that the perception of athletic competence would have a stronger influence on self-worth in the athletic group. SUBJECTS AND METHODS: The Self-perception Profile for College Students was completed by 32 athletes and 13 nonathletes. This profile measures 12 subscales plus Global Self-worth independently and generates scores that reflect the subject's perceived importance of and competence in each of the subscale areas. RESULTS: The athletes rated athletics as more important than did nonathletes, although this trend was nonsignificant when adjusted for age. As age increased, the importance of athletics decreased for both groups. There was a direct relationship between perceived athletic competence and self-worth for the athletes but not for the nonathletes. Variables that accounted for the Global Self-worth score in athletes were perceptions of Competence subscales for Appearance, Social Acceptance, Friendship, and Job. Variables that accounted for the Global Self-worth scores in the nonathletes were perceptions of Competence subscales for Romance, Morality, Humor, and Appearance. The athletic group had significantly lower Global Self-worth scores than the nonathletic group. CONCLUSIONS: The female athletes in this study derived a large component of their self-worth from their perceived athletic competence. Clinicians should bear in mind the relative importance of athletics to young female athletes and the relationship of perceived athletic ability to self-worth when treating these individuals.